The Influence of Top Management Team Composition on Company Performance: The Case of Indonesian Mining Companies - Tulung, Joy Elly (Universitas Prasetiya Mulya, 2009)
Top management team composition is a big issue in international business and management research. In Indonesian context, especially for mining companies, the issue has only limited academic resource. Since most studies in this area conducted in the United States and Europe, the studies are reflecting the culture of the underlying US and Europe population. This research using a sample from 18 Indonesian Mining Companies with 174 top executives from those companies. This study utilizes a deductive method of research as a methodological approach. Each hypothesis analyzes the influence of the composition of the Top Management Team (Independent Variable) on company performance (Dependent Variable), with the relationship made by creating a direct hypothesis of Top Management Team with the value of the return of assets (ROA) and return of equity (ROE) of each company.